Analisis Implementasi Digitalisasi UMKM Melalui Pemetaan Usaha di Google Maps terhadap Peningkatan Akses Pasar : Studi Kasus Desa Ndokum Siroga - Era Rahmadani Damanik; Leni Shofyani; Lisna Berutu; Yunda Fadilla Agustin; Uqbatul Khoir Rambe (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
This study aims to describe the implementation process of MSME digitalization through business mapping on Google Maps and evaluate its impact on improving market access in Ndokum Siroga Village. The approach used was Participatory Action Research (PAR), which directly involved MSMEs, village officials, and students in the process of identifying obstacles, planning, training, and evaluation. Activities included publicizing the importance of digitalization, mentoring in the creation and management of Google Maps accounts, and managing digital content such as product photos and responses to customer reviews. The results indicate increased business visibility, customer interactions, and market expansion, which can boost the competitiveness of micro-enterprises in rural areas. However, challenges faced include a digital literacy gap and limited internet infrastructure, which require ongoing support from the village government and academics. This study demonstrates that the use of geolocation platforms such as Google Maps is an effective, low-cost, and sustainable strategy to support local economic development and strengthen MSME competitiveness in the digital era. It also makes a significant contribution to the sustainability of technology-based village economic development programs.